2020
DOI: 10.1039/d0nh00461h
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured amorphous gallium phosphide on silica for nonlinear and ultrafast nanophotonics

Abstract: A system of amorphous gallium phosphide nanopatches is shown to be a flexible, cheap and efficient platform for ultrafast and nonlinear nanophotonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…The resulting time constants of 32, 33, and 55 fs for 785, 835, and 950 nm probe wavelengths, respectively, evidence the ultrafast nature of the measured modulation. The fact that these values are in the same range as reported for all-optical modulations in dielectric materials [51][52][53] further corroborates the nonlinear nature of the observed signal.…”
Section: S a Maiersupporting
confidence: 85%
See 1 more Smart Citation
“…The resulting time constants of 32, 33, and 55 fs for 785, 835, and 950 nm probe wavelengths, respectively, evidence the ultrafast nature of the measured modulation. The fact that these values are in the same range as reported for all-optical modulations in dielectric materials [51][52][53] further corroborates the nonlinear nature of the observed signal.…”
Section: S a Maiersupporting
confidence: 85%
“…Comparing the maximum change in reflectivity of −0.8% for the NbP film shows this is in the same range as reported values for 2D perovskite nanosheets [ 54 ] and amorphous gallium phosphide thin films. [ 53 ] The temporal traces in Figure 4c reveal another interesting feature of the thin film. At long delay times, a negative to positive sign change is found when increasing the probe wavelength, as noticeable in Figure 4d at a fixed 2 ps delay time.…”
Section: Resultsmentioning
confidence: 99%
“…This material was already subject of previous studies by our group, with ellipsometric and XRD characterization reported in references. [26,27] For electrical contact, the a-GaP is deposited onto a 100 nm thick layer of indium tin oxide (ITO) on an a-SiO 2 substrate. We first demonstrate the spectral tuning of the AE and LR on single particles and 20 × 20 rectangular arrays, both fabricated by electron beam lithography.…”
Section: Introductionmentioning
confidence: 99%
“…These results presented here show great merit for all‐optical switching when weighing the three main considerations of power consumption, switching speed and signal modulation. A comparison with the results in this work to state‐of‐the‐art all‐optical switching platforms [ 11,15,18,22,27–29,45 ] is given in Table 2 . Both the reported differential and absolute modulation values (if readily available) are given from the referenced works to highlight their overall modulation responses and better illustrate the comparison to and significance of this presented work.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16,23,24 ] The latter is enabled by the presence of a direct electronic gap, which facilitates ultrafast relaxation of FCs and showing recombination times as short as several picoseconds. Although typically, indirect band gap materials do not employ efficient FC relaxation pathways to reduce the relaxation time to the sub‐picosecond time scale, [ 1,19,20,25–30 ] amorphous materials [ 29,31 ] have shown promise for nanophotonic devices and ultrafast FC relaxation. The lack of long‐range order in amorphous materials leads to the disappearance of extended states (e.g., Bloch states for electrons) resulting in localized states which leads to a stronger electron–phonon coupling and faster free carrier relaxation.…”
Section: Introductionmentioning
confidence: 99%